Analisis Struktur Modal terhadap Kinerja Keuangan Perusahaan Sektor Utama yang Terdaftar di Indeks LQ45 Bursa Efek Indonesia - Wardani, Arizca Kusuma; Dewi, Farida Ratna (Jurnal Manajemen dan Organisasi, 2015)
The main sectors (industries producing raw materials) of Indonesian Stock Exchange consist of agriculture and mining sectors. The number of primary sector companies listed in LQ45 tend to decrease in each period. Companies included into LQ45 are those with relatively good performance. On the other hand,the proper capital structure policy can optimize the performance of finance companies. The purposes of this research are: 1) to analyze capital structure of the main sector companies; 2) to analyze financial performance of the main sector companies; 3) to analyze theinfluence of capital structure on financial performance of the main sector companies. This research uses primary data from 2009-2013 sector companies with sample selection purposive of sampling technique. Data were analyzed using Structural Equation Modelling. Debt to Assets Ratio, Debt to Equity Ratio, andLong Term Debt to Equity Ratio are the loading factors of latent capital structure. Current Ratio, Quick Ratio, and Cash TurnoverRatio are the loading factors of latent liquidity. Profit Margin, Return on Asset, and Return on Equity are the loading factors of latent profitability. Assets Turnover Ratio, Inventory Turnover Ratio, and Working Capital Turnover Ratio are the loading factors of latent activity. Price Earning Ratiois a loading factor of latent market value. The results show that capital structure has positive and significant effects on activity, negative but not significant effects on liquidity, and significantly negative effects on profitability, but no effect on market value.Keywords: activity, capital structure, liquidity, market value, profitability